If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(0)b=1
We simplify the equation to the form, which is simple to understand
(0)b=1
Reorder the terms in parentheses
(b)=1
Remove unnecessary parentheses
b=1
We move all terms containing b to the left and all other terms to the right.
b=+1
We simplify left and right side of the equation.
b=+1
0=1
The left and right sides are not equal, therefore there is no solution. This equation is invalid.
| 17(y-73)=y-4 | | y=x^3+x^2-16x-16 | | 50x-60= | | -8+7y=-56 | | -3(3y-10)+2(2y+7)= | | 14u^2+5u-1=0 | | 2+5=0 | | -4-(3-5p)= | | 4(3z-1)-2(z+1)=7(z+1) | | -(2z+2)+3(2z+5)-2z= | | -6(n-4)+3(n+1)= | | -7(n-2)+4(n+1)= | | 174=30+12y | | 3=5p(4q-1) | | N+3(n-1)= | | -5x+10x=20 | | 0.5x+0.20(9.0*x)=4.20 | | Ad+9-d-8= | | (0+50)x(1-60-60)x(0+10)= | | 7y+6-12y= | | f(3)=6x+12 | | h(x)=0.10x+9.5 | | 6(u-8)-8u=28 | | 0x+0y=300 | | 2(-3x+5)=4[-4x+5(-x+3)] | | 9(z+3)-3(z-4)=3(z-2)+2(z-1) | | 6(4x-8)-8=6(x-3)+70 | | 2(x+1)-7=3x-15 | | 6x=3(x-2)+33 | | 2(x+2)=5(x-1)-6 | | 7(3n+4)=9(4n+7)+4 | | x+5+x=x+7+x+4+x+11 |